Pembuatan Bioetanol Dari Nira Nipah Menggunakan Bakteri Zymomonas Mobilis Dengan Variasi Pemekatan Medium Dan Waktu Fermentasi - Wahyu Mey Riswanto; Silvia Reni Yenti; Chairul Chairul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The existence of Nypa palm is abundant in Riau province. Nypa can potentially supply biofuels because Its sap has a sugar content of 15-20% which can be converted into bioethanol. Bioethanol is ethanol produced from raw materials containing starch, sugar and cellulose through a process of fermentation and distillation that can be used as an alternative fuel which is environmentally friendly and renewable. To be Able to produce bioethanol from nypa sap in a laboratory scale, it is necessary to study the manufacture of bioethanol from nypa sap through fermentation by using Zymomonas mobilis fermentation medium volume of 2 liters. The objective of the research is to convert the sugar in the nypa sap through fermentation into bioethanol and to observe the effect of concentration medium of the juice in the fermentation and fermentation time on bioethanol production using Zymomonas mobilis. Through the process of fermentation using Zymomonas mobilis, glucose is converted into ethanol and carbon dioxide. Preparation starter was made with yeast inoculum process Zymomonas mobilis at 10% of the fermentation medium, therefore it can be adaptable and ready for fermentation. Fermentation takes place in batches with a volume of 2 liters of fermentation medium, concentration variations sap by evaporation at 10; 20; 30% (v/v) as well as variations in the fermentation time of 12; 24; 36; 48; 60; 72 and 84 hours. Temperature fermentation at room temperatur is 25 – 30oC. Ethanol concentration was Analyzed by using Gas Chromatography. Optimum conditions of bioethanol production from Nypa Sap were shown having 30% concentrated medium variation, and fermentation hours 60th about 15,164 % (v/v) or 111,689 mg/ml.Keywords: bioethanol, concentrated, nypa Sap, zymomonas mobilis